Self-energy effects in electronic Raman spectra of doped cuprates due to magnetic fluctuations - Zeyher, Roland (2013)
We present results for magnetic excitations in doped copper oxides using the random phase approximation and itinerant electrons. In the [1,0] direction the observed excitations resemble dispersive quasiparticles both in the normal and in the superconducting state, similarly to recent resonant inelastic x-ray scattering experiments. In the [1,1] direction the excitations form, except for the critical region near the antiferromagnetic wave vector Q = ( π , π ) , only very broad continua. Using the obtained spin propagators we calculate electron self-energies and their effects on electronic Raman spectra. We show that the recently observed additional peak at about twice the pair breaking in B 1 g symmetry below T c in HgBa 2 CuO 4 + δ can be explained as a self-energy effect where a broken Cooper pair and a magnetic excitation appear as final states. The absence of this peak in B 2 g symmetry, which probes mainly electrons near the nodal direction, is explained by their small self-energies compared to those in the antinodal direction.